Avocado Hass peel from industrial by-product: effect of extraction process variables on yield, phenolic compounds and antioxidant capacity - García-Ramón, Fernando; Malnati-Ramos, Miguel; Rios-Mendoza, Jesaya; Vivar-Méndez, Jorge; Nieva-Villegas, Lilia María; Cornelio-Santiago, Heber Peleg; Sotelo-Méndez, Alejandrina (Frontiers in Sustainable Food Systems, 2023)
At present in Peru, a substantial quantity of avocado by-products (peel and seed) is produced due to avocado processing. It is essential to revalue these products. The meticulous selection of parameters in solid–liquid extraction through maceration, which is the industrial preference, is crucial to obtain a greater recovery of phenolic compounds from avocado Hass peels. Therefore, the aim of this study was to assess the impact of process variables (ethanol concentration, temperature and solvent:feed (S/F) ratio) on the global yield of extraction (GY), total phenolic content (TPC), total flavonoid content (TFC), and antioxidant capacity (DPPH) of avocado Hass peel extract at two different stages of maturity. Furthermore, the quantification of phenolic compounds was using High Performance Liquid Chromatography with Diode Array Detection (HPLC-DAD) and antioxidant capacity using ABTS and FRAP assays were determined in higher yielding extracts. The dry matter content (dm) was determined in the pulp of unripe avocados (UA, 22.57% dm) and ripe avocados (RA, 27.30% dm). The results showed that, for all treatments, ethanol concentration, temperature, S/F ratio had a significant influence (p < 0.05) on GY, TPC, TFC and antioxidant capacity, and the UA peel extracts obtained with 40% ethanol, 49.3°C, S/F ratio (14.3 mL/g) and 60 min showed the highest values of TPC (44.24 mg GAE/g peel dw), TFC (786.08 mg QE/g peel dw) and antioxidant capacity against DPPH (564.82 μmTE/g peel dw), ABTS (804.40 μmTE/g peel dw) and FRAP (1006.21 μmTE/g peel dw). Meanwhile, for the HPLC-DAD analysis, vanillic acid and 4-hydroxyphenylacetic acid are the main phenolic compounds present in avocado peel extracts. The results of this research indicate that avocado peels are a source of natural phenolic components, with potential application in the food industry as a viable alternative to synthetic antioxidants, thus reducing their use.